EVALUASI FUNGSI LINGKUNGAN EMBUNG BERBASIS SISTEM INFORMASI GEOGRAFI: KASUS EMBUNG KRAPYAK DAN TONOGORO DI KULON PROGO, DAERAH ISTIMEWA YOGYAKARTA (Environment Role Evaluation of Retention Basins Using Geographic Information Systems: Case of Krapyak and Tonogoro in Kulon Progo, Special Region of Yogyakarta) - Marina Yuliarti; Ngadisih; M. Pramono Hadi; Junun Sartohadi; M. Anggri Setiawan (Asosiasi Peneliti dan Teknisi Kehutanan dan Lingkungan Hidup Indonesia (APTKLHI), 2023)
Environmentally, retention basins are used for soil and water conservation but some of them experience drought. The location of the retention basin is fundamental in fulfilling environmental functions. This study aimed to apply GIS for evaluating the environmental functions of retention basins in a certain area. Tonogoro and Krapyak retention basins lay on Kulon Progo Regency, Yogyakarta are the cases of this study. The Krapyak is located at the outlet of catchment area, while the Tonogoro is built on the hilltop. Environmental functions were assessed based on the potential drought and dynamics of carrying capacity due to sedimentation. The materials used were detailed design documents, Google Earth images, DEMNAS images, 1:25,000 scale Indonesian landform maps, rainfall data, and soil type maps. The initial reservoir capacity was calculated based on depth using DEMNAS data. The recent reservoir capacity was measured using a sounding method with a Garmin 520s Echo sounder, Depth Sounder, and Roll meter. All data was integrated in GIS to be presented visually in the form of a reservoir depth profile that reflects the dynamics of the reservoir capacity. The potential of surface runoff volume was calculated using SCS-CN method. This study found that the Tonogoro retention basin experienced a water shortage because the potential volume of runoff water was only able to supply 5% of the reservoir’s capacity. The accumulated sediment yield in the Krapyak retention basins was 3,498 m3 or 12.2% of the total capacity of a sedimentation rate of 699.6 m3 per year.